Recall bias secondary to major trauma: results from a prospective study of the Beirut Port Blast - Elie G. Karam; Josleen Al Barathie; Franshesca Hayek; Franco Mascayano; Ezra Susser; Richard Bryant (European Journal of Psychotraumatology)
Background: Traumatic events are often perceived as unforgettable, yet scientific evidence highlights the complexity of memory recall in the aftermath of traumatic experiences. While some studies observed amplification of traumatic memory, others reveal rapid forgetfulness and falsification of details.Objective: The primary objective of this study is to investigate how initial memories of the Beirut Port Blast in 2020 fluctuate over time. Going beyond full-threshold self-reported post-traumatic stress disorder (PTSD) and self-reported acute stress disorder (ASD), the research aims to explore subthreshold self-reported PTSD and individual self-reported ASD symptoms as potential predictors of recall bias among healthcare workers.Method: This study draws on data from four waves of the ongoing B.L.A.S.T. (Beirut Longitudinal Assessment Study of Trauma) study which spans so far over a period of two years.Results: Being a clinical professional and having higher self-reported ASD symptoms in wave 1, specifically intrusion symptoms, were associated with recall diminishment. Higher self-reported PTSD, subthreshold self-reported PTSD diagnoses (six plus or majority) and higher anxiety scores were significantly associated with exaggeration of recall.Conclusion: The study underscores the importance of assessing a broad range of symptoms, beyond conventional diagnoses, to gain a comprehensive understanding of how traumatic memories are recalled and potentially altered over time.